Spintherobolus papilliferus in the rio Ribeira de Iguape basin: implications for the biogeography and conservation of an endangered species (Ostariophysi: Characiformes) - Mattox, George M. T.; Cetra, Mauricio; Souza, Camila S. [UNESP]; Oyakawa, Osvaldo T.; Bento, Rodrigo M. M.; Oliveira, Claudio [UNESP] (FapUNIFESP (SciELO), 2023)
Spintherobolus papilliferus is an endangered characid endemic of the Atlantic Rainforest, known from sparse locations in the upper rio Tietê basin around the metropolitan area of São Paulo city, and from an affluent of rio Itapanhaú, a coastal stream in Bertioga, São Paulo State. In 2020, S. papilliferus was sampled from the rio Ribeira de Iguape basin in Juquitiba, São Paulo State, representing a new distributional record. We compared 17 morphometric and six meristic characters from all specimens with data from the rios Tietê and Itapanhaú. An overlap in the morphological data from the three populations was detected, except for five measure whose values are lower in rio Ribeira de Iguape. MANOVA and LDA revealed that this population differs significantly from the other two, showing shallower body and caudal peduncle, among other features. These morphological differences may be due to environmental selective pressures since rio Ribeira de Iguape drainage is marked by fast waters which can influence the shape of fish bodies over time. DNA-barcoding of all Spintherobolus species corroborate that the rio Ribeira de Iguape population belongs to S. papilliferus. We also present a hypothesis for the disjunct distribution of S. papilliferus involving headwater capture and discuss the implications for the conservation of this endangered species.
Keywords: Atlantic rainforest; Distributional pattern; DNA barcode; Morphometry